Factors Affecting English Speaking Skills: Evidence from Graduate Students in Rawalpindi - Hajra Arshad; Dr. Ejaz Mirza; Dr. Muhammad Farooq Alam (University of Chitral Journal of Linguistics and Literature, 2022)
The aim of this research was to find the factors affecting the speaking skills of graduate students. The study was conducted in the selected institutions of Rawalpindi and Islamabad. The objectives of the study were to identify the factors affecting the speaking skills of graduate students and to analyze the students’ and teachers’ perceptions of the factors affecting speaking skills. The sample included 100 students from three institutions. Questionnaires were used to get the information from the graduate students studying English and the English teachers. The data were analyzed using the Statistical Package of Social Sciences (SPSS) program. Analyzed data were presented descriptively using graphs. The results of the study show that students make errors when they speak English. Future researchers can carry out experimental research to find how different English language teaching method help students to acquire better English-speaking skills.